Analysis of the Influence of Fabrication Errors on the Far-Field Performance of Si and Si3N4 Antennas - Yifan Xin; Wenyuan Liao; Lei Yu; Pengfei Ma; Zheng Wang; Yibo Yang; Licheng Chen; Pengfei Wang; Yejin Zhang; Jiaoqing Pan (Photonics, 2024)
Antennas are important components in optical phased arrays. However, their far-field performance deteriorates when random phase noise is introduced because of fabricating errors. For the first time, we use a finite-difference time-domain solution to quantitatively analyze the far-field characteristics of Si and Si3N4 antennas considering process errors. Under rough surface conditions based on a fishbone structure, we find that the quality of the main lobe of the Si antenna deteriorates badly, with −0.87 dB and −0.51 dB decreases in the sidelobe level and 5.78% and 3.74% deteriorations in the main peak power in the φ (phase-controlled) and θ (wavelength-controlled) directions, respectively. However, the Si3N4 antenna is only slightly impacted, with mere 0.39% and 0.71% deteriorations in the main peak power in the φ and θ directions, respectively, which is statistically about 1/15 of the Si antenna in the φ direction and 1/5 in the θ direction. The decreases in the sidelobe level are also slight, at about −0.08 dB and −0.01 dB, respectively. Furthermore, the advantages of the Si3N4 antenna become more remarkable with the introduction of random errors into the waveguide width and thickness. This work is of great significance for the design and optimization of OPA chips.